2014
DOI: 10.12720/joaat.1.1.60-64
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Profile during Rice (Oryza Sativa) Production

Abstract: Rice (Oryza sativa) is the foremost cereal crop in Southeast Asia. It serves as staple food, thus has a major contribution to the calorie intake. In addition, rice contains melatonin which is beneficial for human health. It is, therefore, essential to retain this compound by appropriate rice production processes. Melatonin profile during rice production was monitored for three varieties (IR64, umbulumbul and pandan wangi) from conventional farming and four varieties (batang lembang, pandan wangi, black and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…We also determined the levels of melatonin and tryptophan in rice and corn extracts. Previously, there was a study revealing the level of melatonin content in black rice at 140 μg/kg (Manchester et al 2000;Hernandez-Ruiz & Arnao 2008;Setyaningsih et al 2014). Our results demonstrated that the highest levels of melatonin content were detected in black rice extracts from ethanol fraction at 396.38 μg/kg.…”
Section: Discussionsupporting
confidence: 56%
“…We also determined the levels of melatonin and tryptophan in rice and corn extracts. Previously, there was a study revealing the level of melatonin content in black rice at 140 μg/kg (Manchester et al 2000;Hernandez-Ruiz & Arnao 2008;Setyaningsih et al 2014). Our results demonstrated that the highest levels of melatonin content were detected in black rice extracts from ethanol fraction at 396.38 μg/kg.…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, this step includes a bran removal process that causes a disadvantage due to the loss of melatonin from the grain, as shown by studies of the melatonin profile during rice production. 44…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Hence, rice is extremely important, not only to satisfy hunger but also to provide nutrients for the population of Indonesia. Several health-benefited substances have been identified in rice and these include melatonin (Setyaningsih et al, 2014). Melatonin (N-acetyl-5-methoxytryptamine) is an indoleamine that is synthesized from the essential amino acid L-tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“…The whole grain (brown) rice, as well as pigmented (red and black) varieties contain higher levels of melatonin than the polished (white) grain. The level of melatonin in these unpolished rice grains is maintained in the final product because there is no bran removal process (Setyaningsih et al, 2014;Setyaningsih et al, 2016). Henceforth, consumption of whole grain (brown, red, and black) rice has additional functional benefit.…”
Section: Introductionmentioning
confidence: 99%